A computational framework and sensitivity analysis for the hormonal treatment of bone. (March 2020) - Idrees, Muhammad; Sohail, Ayesha
Abstract: Background: Osteoporosis is a bone disease identified by disordering of bone formation and resorption cells. It increases the risk of bone fragility and fracture. Autocrine and paracrine signalling of osteoclasts and osteoblasts plays an important role in the regulation of bone remodelling. Calcitonin is an approved pharmacologic agent for the treatment of osteoporosis. Methods: A novel mathematical model comprising the interaction among osteoclasts and osteoblasts cells with intermittent administration of calcitonin has been presented to study the dynamics of osteoporotic bone. The stability of model and sensitivity of parameters are also discussed. Findings: The population of osteoclastic and osteoblastic cells has been predicted via numerical simulation. The results of Monte Carlo sensitivity analysis are shown via tornado diagram. Interpretation: It is concluded that intermittent administration of calcitonin is an effective therapy for the treatment of osteoporosis. Highlights: We focus on the impact of calcitonin and its intermittent input. We discuss the stability of the model with the help of Lyapunov stability theory. We also discuss the sensitivity analysis of our proposed model by using the Monte Carlo method . Clinical trials and their conclusions are revisited for Analysis. A novel mathematical model is synchronised with Sensitivity-Analysis. Dose rates for intermittent therapy, relative to time are presented.